COVID19 antibody detection using lateral flow assay tests in a cohort of convalescent plasma donors - Brett Ragnesola; Daniel Jin; Christopher C. Lamb; Beth H. Shaz; Christopher D. Hillyer; Larry L. Luchsinger (BMC Research Notes, 2020)
Abstract Objective COVID19 has caused a global and ongoing pandemic. The need for population seroconversion data is apparent to monitor and respond to the pandemic. Using a lateral flow assay (LFA) testing platform, the seropositivity in 63 New York Blood Center (NYBC) Convelescent Plasma (CP) donor samples were evaluated for the presence of COVID19 specific IgG and IgM. Results CP donors showed diverse antibody result. Convalescent donor plasma contains SARS-CoV-2 specific antibodies. Weak antibody bands may identify low titer CP donors. LFA tests can identify antibody positive individuals that have recovered from COVID19. Confirming suspected cases using antibody detection could help inform the patient and the community as to the relative risk to future exposure and a better understanding of disease exposure.